BETAH board game based on the 3CM learning model to enhance elementary students’ critical thinking skills - Ginting, Ribka; Wahyudi, Wahyudi; Mawardi, Mawardi (Indonesian Journal of Science and Mathematics Education, 2026)
Elementary school students’ critical thinking skills remain relatively low due to teacher-centered learning that provides less challenging learning experiences. This study aimed to develop and examine the effectiveness of the BETAH board game in improving students’ critical thinking skills. The study employed a Research and Development (R and D) method using the ADDIE model, combined with a quasi-experimental pretest–posttest control group design. The participants were second-grade students from five elementary schools in Bandar Lampung. The research instruments included expert validation sheets, teacher response questionnaires, and a critical thinking skills test. The results showed that the developed media was valid and practical based on expert judgment and teacher responses. Quantitatively, the mean score increased from 60.74 in the pretest to 78.51 in the posttest, with a mean difference of 17.77, which was statistically significant based on the t-test (p < 0.05). These findings indicate that the integration of the BETAH board game with the 3CM learning model is effective in improving students’ critical thinking skills. Therefore, the developed media can serve as an alternative instructional tool to support critical thinking development in elementary mathematics learning.